Structural and electronic properties of defects at grain boundaries in CuInSe2. Issue 22 (26th May 2017) - Saniz, R.; Bekaert, J.; Partoens, B.; Lamoen, D.
Abstract : Octet rule violation near the grain boundary plane is common in Σ3 grain boundaries, with important structural and electronic implications. Abstract : We report on a first-principles study of the structural and electronic properties of a Σ3 (112) grain boundary model in CuInSe2 . The study focuses on a coherent, stoichiometry preserving, cation–Se terminated grain boundary, addressing the properties of the grain boundary as such, as well as the effect of well known defects in CuInSe2 . We show that in spite of its apparent simplicity, such a grain boundary exhibits a very rich phenomenology, providing an explanation for several of the experimentally observed properties of grain boundaries in CuInSe2 thin films. In particular, we show that the combined effect of Cu vacancies and cation antisites can result in the observed Cu depletion with no In enrichment at the grain boundaries. Furthermore, Cu vacancies are unlikely to produce a hole barrier at the grain boundaries, but Na may indeed have such an effect. We find that Na-on-Cu defects will tend to form abundantly at the grain boundaries, and can provide a mechanism for the carrier depletion and/or type inversion experimentally reported.